Association of tooth wear to temporomandibular joint disorders and sleep breathing disorders in Indian school children. - Bhalgat, Satish. (2017)
Abstract: Aim: The aim of this study was to find if any association exists between the non- carious tooth wear, temporomandibular disorders and sleep breathing disorders in children. Introduction: Tooth wear, temporomandibular disorders (TMD) and sleep breathing disorders (SBD) are some common disorders in adults as well as children. These conditions may be present either alone or in combination. Sometimes these disorders remain undiagnosed for a long time, especially in children as they may not realize that this discomfort is pathological. Early detection of these disorders may positively impact a child's growth and overall health. Methods: This cross-sectional observational study included 1009 Indian school children. Validated indices like Helkimo Index and Sleep Disorder Scale for Children by Bruni for SBD were used to determine TMD and SBD respectively. A child was considered tooth wear positive if any of the tooth surfaces presented tooth wear. Associations between these three conditions were evaluated using chi-square tests. All analyses were performed using SAS, Version 9.2 (SAS Institute, Cary, NC). Results: 1009 subjects, 405 girls and 604 boys between 10 years and 16 years of age formed the sample of the study. Mean (standard deviation) age was 12.8 (0.78) years. Of the 1009, 853 (84.5%) had tooth wear (661 mild and 192 severe), 356 (35.3%) had sleep breathing disorders, 587 (58.2%) had clinically diagnosed temporomandibular disorders, and 371 (36.8%) had self-diagnosed temporomandibular disorders. Of the 356 with sleep breathing disorders, 253 (71.1%) had clinically diagnosed temporomandibular disorders, compared to 334 of the 653 (51.1%) without sleep breathing disorders. This was a statistically significant difference. Of the 853 with tooth wear, 492 (57.7%) had clinically diagnosed TMD as compared to 95 of the 156 (60.9%) with no tooth wear. This was not a statistically significant difference. Of the 853 with tooth wear, 307 (36%) had sleep breathing disorders, compared to 49 of the 156 (31.4%) with no tooth wear. This was also not statistically significant difference. Conclusion: This study concludes that there is a high prevalence of tooth wear, sleep breathing disorders and temporomandibular disorders in Indian school children. There is statistically significant association between sleep breathing disorders and temporomandibular disorders and there may be no significant association between tooth wear and sleep breathing disorders and temporomandibular disorders.; Thesis (M.S.)--Tufts University, 2014.; Submitted to the Dept. of Other.; Advisors: Noshir Mehta, and Brijesh Chandwani.; Committee: Paul Stark, Ronald Kulich, and Tofool Alghanem.; Keywords: Medicine, Asian studies, and Health sciences.